Cell adhesion molecules in subretinal fluid: soluble forms of VCAM-1 (vascular cell adhesion molecule-1) and L-selectin - TOKER, AYŞE EBRU (My University, 1998)
PURPOSE: In this study we investigated the presence of soluble VCAM-1 and soluble L-selectin-1 in subretinal fluids (SRF) of patients suffering from rhegmatogenous retinal detachment . METHOD: Subretinal fluids were collected from drainage sclerotomies during surgery from 27 patients with rhegmatogenous retinal detachment complicated by proliferative vitreoretinopathy (PVR) or uncomplicated retinal detachment. Levels of sVCAM-1 and sL-selectin-1 were quantified with ELISA. RESULTS: The mean +/- SEM values of sVCAM-1 and sL-selectin-1 were 222.2 +/- 81 ng/ml and 171.7 +/- 42.1 ng/ml, respectively. The concentrations of sVCAM-1 in patients with Grade C PVR (498.2 +/- 1703 ng/ml) were significantly different from those with Grade B PVR (45.6 +/- 16.5 ng/ml) and uncomplicated retinal detachments (19.4 +/- 12.3 ng/ml). SVCAM-1 concentration in detachments which had been present for more than 8 weeks was 738.8 +/- 431 ng/ml, significantly higher than the levels in detachments of shorter duration (132.4 +/- 47.7 ng/ml). sL-selectin-1 level in Grade C PVR (291.6 +/- 92.8 ng/ml) was higher than in uncomplicated retinal detachments (72.8 +/- 13.5 ng/ml). Significantly elevated levels of sL-selectin-1 were observed in detachments lasting more than 8 weeks (605 +/- 151.1 ng/ml) compared to those of shorter duration (96.3 +/- 13.1 ng/ml). CONCLUSION: The present study supports growing evidence that these cell adhesion molecules are involved in the inflammatory process during the development and progression of PVR.
Keywords: Adult; Female; Humans; Middle Aged; Prognosis; Aged; Adolescent; Male; Follow-Up Studies; Biomarkers; Retinal Detachment; Enzyme-Linked Immunosorbent Assay; Disease Progression; Ophthalmologic Surgical Procedures; Body Fluids; Retina; L-Selectin; Vascular Cell Adhesion Molecule-1; Vitreoretinopathy, Proliferative